Positive correlation between the Po River discharge and ocean colour trends of Chl and TSM in the Adriatic Sea - Vona, Iacopo; Colella, Simone; Sammartino, Michela; Brando, Vittorio E.; Falcini, Federico (Frontiers in Remote Sensing, 2025)
Coastal areas represent delicate and complex environments due to the interconnection between land and sea, where marine, fluvial and anthropogenic stressors combine threatening and undermining coastal health. Sea level rise and increasing storminess, for instance, lead to more frequent coastal flooding and habitat loss due to erosion; sediment supply by rivers, on the other hand, helps coastal areas to balance and restore habitat loss. However, excessive riverine nutrient inputs may lead to coastal eutrophication phenomena, putting coastal ecosystem as well as coastal communities at serious risk. Here, we compute high resolution (300 m) Chlorophyll-a (Chl) and Total Suspended Matter (TSM, a proxy for sediment concentration) trends over the Adriatic Sea by using the single sensors MERIS (from 2003 to 2012) and OLCI (from 2017–2024) data, to study the response of the marine ecosystem to human and/or environmental pressures, and thus for detecting coastal areas likely subject to eutrophication and/or sediment starvation. Such an analysis is complemented by Po River discharge data to investigate the role of river outputs in shaping the observed trends within the Adriatic basin. Our results reveal Chl and TSM trends in the northern part of the Adriatic basin being positively correlated with the Po River discharge during the investigated period, for both MERIS and OLCI data. Increases/decreases in the Po River outflow resulted in positive/negative Chl and TSM trends. Although a negative trend of Chl was documented within the Adriatic Sea in the last 25 years, Po River load fluctuations regulate long- and short-term, local trends of both Chl and TSM in the North Adriatic basin. This result suggests a direct relationship existing between river discharge and statistical trends of TSM and Chl in delta areas.